KRUNA WILANGAN BASA BALI KUNO SAJERONING KAMUS BASA BALI KUNO LAN PEPADANNYANE RING BASA BALI ANYAR - Suastika, Komang Endy; Paramarta, I Ketut; Purnami, Ida Ayu Putu (Universitas Pendidikan Ganesha, 2019)
This study aims to describe (1) type of numbers in old Balinese, and (2) type of numbers in new Balinese. The subject of this study is the ancient Balinese inscription while the object is the numbers. The documentation method is used in order to collect the data. Then, the data analysis uses several techniques such as, data identification, data reduction, data classification, and data summarization. The result of this study was found that (1) type of the numbers in the old Balinese such as distributive numbers, collective numbers, indefinite distributive numbers, klitik numbers, measurement numbers, and fractional numbers, and (2) type of numbers in New Balinese which based on the same meanings, such as the equivalent forms, the similar forms, and the different forms.